The effect of the arousal threshold on sleep bruxism intensity in coexisting sleep apnea and sleep bruxism: a polysomnographic study - Helena Martynowicz; Karol Marschollek; Dorian Nowacki; Justyna Kanclerska; Gabriella Lachowicz; Anna Jodkowska; Piotr Macek; Weronika Frosztęga; Katarzyna Madziarska; Marta Waliszewska-Prosół (Scientific Reports)
Abstract Obstructive sleep apnea (OSA) is often accompanied by sleep bruxism (SB). A low respiratory arousal threshold (AT) may contribute to the induction or exacerbation of SB. The aim of this study was to assess the impact of the AT on the intensity of bruxism in individuals with OSA and SB. The prospective observational study was undertaken in 117 subjects with suspected sleep disorder (47% females, average age 44.83 years) who undergone video-polysomnography. Among the study participants, 77 (64.1%) were found to have a low AT, while 42 (35.9%) had a high AT. Participants with low AT’s had significantly higher bruxism episode index (BEI) and phasic BEI values than patients with a high AT (6.06 ± 4.46 vs. 4.54 ± 3.18; p = 0.04 and 3.18 ± 3.49 vs. 1.84 ± 1.74; p = 0.03, respectively). The positive correlation between BEI and a low AT and a higher percentage of hypopneas were found (R = 0.190, p = 0.040; R = 0.278, p = 0.002, respectively). Summarizing, there is a higher intensity of SB observed in patients with a low AT, than in those with a high one. This effect is more pronounced in men. SB accompanying low AT may be a protective factor in OSA patients, by terminating respiratory events. Thus patients with a low AT and SB could be better protected from OSA complications.